Decolonizing Aboriginal Education in the 21st Century - Munroe, Elizabeth; Borden, Lisa; Murray Orr, Anne; Toney, Denise; Meader, Jane (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
Concerned by the need to decolonize education for Aboriginal students, the authors explore philosophies of Indigenous ways of knowing and those of the 21st century learning movement. In their efforts to propose a way forward with Aboriginal education, the authors inquire into harmonies between Aboriginal knowledges and tenets of 21st century education. Three stories from the authors’ research serve as examples of decolonizing approaches that value the congruence between 21st century education and Indigenous knowledges. These stories highlight the need for two-eyed seeing, co-constructing curriculum for language and culture revitalization, and drawing from community contexts to create curriculum.